Factors Influencing Farmers' Motivation In Earning Porang (Amorphophallus Muelleri) In Ulusena Village Moramo District, South Konawe District - Wa Ode Muswanti; Rosmawati Rosmawati; La Ode Kasno Arif (Cita konsultindo, 2023)
This research aims to: (1) find outthe level of motivation of farmers in cultivating porang, (2) knowing the factors related to farmer motivation in cultivating porang. The research location was carried out in Ulusena Village, Moramo District, South Konawe Regency from July to December 2022. The research location was chosen purposively with the consideration that Ulusena Village is the place that cultivates the most porang plants.PThe population in this research were all porang farmers in Ulusena Village, Moramo District, South Konawe Regency, totalingas much150K.K.Sample determination was carried out by simple random (simplement random sampling).Based on the Slovin formula calculation, a sample size of 35 people was obtained.The variables in this research are independent variables including age, formal education, non-formal education, farming experience, land area, number of family dependents, expenses, and income and the dependent variables include economic motivation and sociological motivation.The results of the research show that (1) the level of motivation of porang farmers in Ulusena Village, Moramo District, South Konawe Regency with a percentage of 93.24 is categorized as high, (2) factors related to the motivation of porang farmers in Ulusena Village, Moramo District, South Konawe Regency are age, non-formal education, farming experience, land area, and income, because the significance value is <0.05, the relationship between the two variables is said to be significant, so the two variables are interconnected between the motivational factors of farmers in cultivating porang.